Increased Risk of Upper Respiratory Infection in Military Recruits Who Report Sleeping Less Than 6 h per night. Issue 11 (9th May 2018) - Wentz, Laurel M; Ward, Mark D; Potter, Claire; Oliver, Samuel J; Jackson, Sarah; Izard, Rachel M; Greeves, Julie P; Walsh, Neil P
Abstract: Introduction: Professional sleep associations recommend 7–9 h of sleep per night for young adults. Habitually sleeping less than 6 h per night has been shown to increase susceptibility to common cold in otherwise healthy, adult civilians. However, no investigations have examined the importance of sleep duration on upper respiratory tract infection (URTI) and loss of training days in military recruits. The purpose of this study was to describe self-reported sleep duration in a large cohort of military recruits and to assess the relationship between reported sleep duration and incidence of URTI's. We hypothesized that recruits who reported sleeping less than the recommended 7–9 h per night during training suffered a greater incidence of URTI and, as a consequence, lost more training days compared with recruits who met sleep recommendations. Materials and Methods: Participants included 651 British Army recruits aged 22 ± 3 yr who completed 13 wk of basic military training (67% males, 33% females). Participants were members of 21 platoons (11 male, 10 female) who commenced training across four seasons (19% winter, 20% spring, 29% summer, and 32% autumn). At the start and completion of training, participants completed a questionnaire asking the typical time they went to sleep and awoke. Incidence of physician-diagnosed URTI and lost training days due to URTI were retrieved from medical records. Results: Self-reported sleep duration decreased from before to during training (8.5 ± 1.6 vs. 7.0 ± 0.8 h; p < 0.01). Prior to training, 13% of participants reported sleeping less than the recommended 7 h sleep per night; however, this increased to 38% during training ( X 2 = 3.8; p = 0.05). Overall, 49 participants (8%) were diagnosed by a physician with at least one URTI and 3 participants (<1%) were diagnosed with two URTI's. After controlling for sex, body mass index, season of recruitment, smoking, and alcohol, participants who reported sleeping less than 6 h per night during training were four times more likely to be diagnosed with URTI compared with participants who slept 7–9 h per night in a logistic regression model (OR 4.4; 95% CI, 1.5–12.9, p < 0.01). On average, each URTI resulted in 2.9 ± 1.5 lost training days. Participants who were diagnosed with URTI had more overall lost training days for any illness compared with participants who did not report a URTI during basic military training (3.3 ± 1.9 vs. 0.4 ± 1.3; p < 0.01). Conclusion: In a large population of British Army recruits, these findings show that more than one third of participants failed to meet sleep duration recommendations during training. Furthermore, those who reported sleeping less than 6 h per night were four times more likely to be diagnosed with an URTI and lost more training days due to URTI. Since sleep restriction is considered a necessary element of military training, future studies should examine interventions to reduce any negative effects on immunity and host defense.